The Madrasah Head's Strategy in Developing Radhiatul Adawiyah Mangga Tiga Makassar Madrasah Aliyah - Eva Sri Rohani; Muh. Natsir; Fita Dewi Yuniar; Rosika Indri Karadona (Edusoshum : Journal of Islamic Education and Social Humanities, 2025)
This research focuses on the Strategy of the Head of Madrasah Aliyah Radhiatul Adawiyah Mangga Tiga Makassar. This research aims to: (1) To analyze the strategy of the head of madrasah in the development of Madrasah Aliyah Radhiatul Adawiyah Mangga Tiga Makassar, (2) To identify the supporting and inhibiting factors in the development of Madrasah Aliyah Radhiatul Adawiyah Mangga Tiga Makassar. The problem formulations are: (1) What is the strategy of the Head of Madrasah in the Development of Madrasah Aliyah Radhiatul Adawiyah Mangga Tiga Makassar? (2) What are the Supporting and Inhibiting Factors in the Development of Madrasah Aliyah Radhiatul Adawiyah Mangga Tiga Makassar? Can the head of madrasah's strategy develop the madrasah in accordance with the arrangements made by the head of madrasah or the madrasah itself? This research uses a qualitative approach, and the approach used is a case study approach that only focuses on the madrasah. Data collection was carried out using observation, interview, and documentation methods. The collected data is then processed through data reduction, data presentation, and conclusion drawing. From the research results, it can be concluded that. The results showed that the head of madrasah implemented several main strategies, namely: (1) formulating the vision and mission of the madrasah in a participatory manner; (2) improving the quality of teachers through routine training and internal coaching; (3) improving facilities and infrastructure gradually according to needs; (4) building partnerships with the community, madrasah committee, and external institutions; (5) as well as instilling a religious culture and discipline in all madrasah members. These strategies have proven effective in the development of Madrasah Aliyah Radhiatul Adawiyah Mangga Tiga Makassar.